Pengembangan Media Berbasis Wordwall pada Materi Terminologi Pembuatan Rok pada Mata Pelajaran Teknik Dasar Menjahit - Harianto, Alvi Anggraini; Irianti, Agus Hery Supadmi; Sulistyaningwati, Bhindri; Apriliyanawati, Adila; Rahayu, Alimah (Universitas Nusantara PGRI Kediri, 2025)
Understanding fashion terms or terminology is an important thing to be mastered by teachers and students of the Fashion Design and Production expertise program, to facilitate communication in the learning process so that there are no mistakes in the practice of making clothes. Learning about fashion terminology can be done with the help of interactive learning media. An example of media that can be used is Wordwall-based media. This study aims to 1) develop Wordwall-based media on the terminology material for making skirts in the Basic Sewing Techniques subject, 2) determine students' responses to Wordwall-based learning media. This development research method uses the ADDIE model development technique, where for validation using expert validation using the formula Vah = (TSE: TSH) x 100%. While the implementation was carried out on class X DPB 3 students where respondents were taken using a saturated sampling technique of 32 students, the analysis technique used a percentage technique with the formula Percentage = (Number of scores obtained: Maximum number of scores) x 100%. The validation results showed 89.6% with a very feasible category. The implementation results obtained 88.06% with a very good category, which means that this media makes it easier for students to learn the material on making skirts.